Kualitas Air dan Perilaku Masyarakat Terhadap Derajat Kesehatan Masyarakat - Adilla Dwi Nur Yadika (CV. Jasa Sukses Abadi, 2026)
Water quality is a crucial factor in maintaining public health. The quality of water is crucial for daily life, from drinking to household, industrial, and health needs. Water that does not meet standards can cause various infectious and chronic diseases. This article uses a literature approach through a review of various studies related to water quality parameters and their impact on health. Water quality can be measured using the Water Quality Index (WQI). Parameters that determine water quality include physical, chemical, and biological factors. Low water quality is associated with high levels of heavy metals (Pb, As, Fe, Cd), chemical compounds (nitrate and fluoride), and microbiological contamination (Escherichia coli). Water quality can be influenced by natural factors, such as rainfall, watershed geography, the atmosphere, and geology. Furthermore, water quality is also determined by community behavior, which in turn influences community health, such as industrial, domestic, and/or agricultural activities. Community behavior in water treatment and storage also influences the increased risk of diarrhea, cholera, and nervous system disorders. Water quality and community behavior play a significant role in community health. Cross-sectoral collaboration between government, industry, and the community is needed to maintain water quality and prevent waterborne diseases, thereby improving public health.